Long-term management of advanced basal cell carcinoma: current challenges and future perspectives - Heppt, Markus V.; Gebhardt, Christoffer; Hassel, Jessica C.; Alter, Mareike; Gutzmer, Ralf; Leiter, Ulrike; Berking, Carola (Cancers, 2022)
The first-line therapy for locally advanced basal cell carcinoma (laBCC) is Hedgehog pathway inhibitors (HHIs), as they achieve good efficacy and duration of response. However, toxicity in the course of long-term treatment may lead to a decrease in the quality of life, and consequently to interruption or even discontinuation of therapy. As HHI therapy is a balancing act between effectiveness, adverse events, quality of life, and adherence, numerous successful treatment strategies have evolved, such as dose reduction and dose interruptions with on-off treatment schedules or interruptions with re-challenge after progression. As a small percentage of patients show primary or acquired resistance to HHIs, the inhibition of programmed cell death protein 1 (PD-1) has been approved as a second-line therapy, which may also be accompanied by immune-related toxicities and non-response. Thus, optimization of current treatment schedules, novel agents, and combination strategies are urgently needed for laBCC. Here, we narratively model the treatment sequence for patients with laBCC and summarize the current state of approved treatment regimens and therapeutic strategies to optimize the long-term management of laBCC.
Gesehen am 11.01.2023